Implementation of an EFQM model in a higher education institution in Portugal - Santos, Ricardo (2019)
In an increasingly competitive sector, such as education, higher education institutions depend more and more on the quality of services provided, given that the success achieved through quality management does not depend only on the recognition of their users, but increasingly, the attractiveness of financing, ensuring the present and future sustainability of the organization. In this way, it is not enough just to meet the "minimum quality requirements", but rather to exceed the expectations created, which creates difficulties, given the very organizational nature of the HEI. In view of the challenge created, HEIs tend to incorporate Internal Quality Assurance Systems (IQAS) into their strategy with a view to continuous improvement of their performance. Using the methodology of the case study, the present work intends to analyze the applicability of a IQAS in the organizational performance of an HEI, based on the model of the European Foundation for Quality Management (EFQM), and implemented in a School of Engineering in Portugal. We try to contribute with a critical analysis to the viability of the application of the model under study, highlighting in the end some identified advantages, as well as some difficulties found, that can be overcome from a set of measures suggested here. Num setor cada vez mais competitivo, como o do ensino, as Instituições de Ensino Superior (IES), dependem cada vez mais, da qualidade dos serviços prestados, dado que o sucesso obtido através da gestão de Qualidade, não depende apenas do reconhecimento dos seus utilizadores, mas sim e cada vez mais, da capacidade de atração de financiamento, assegurando a sustentabilidade presente e futura da organização. Deste modo, não basta apenas, satisfazer os “requisitos mínimos de qualidade”, mas sim, superar as expectativas criadas, o que levanta dificuldades, dada a natureza organizacional muito própria das IES. Atendendo ao desafio criado, as IES, tendem a incorporar na sua estratégia, Sistemas Internos de Garantia da Qualidade (IQAS), com vista a melhoria contínua, do seu desempenho. Recorrendo à metodologia de estudo de caso, pretende-se com o presente trabalho, analisar a aplicabilidade de um IQAS no desempenho organizacional de uma IES, baseado no modelo da European Foundation for Quality Management (EFQM), e implementado numa Escola de Engenharia em Portugal. Procura-se contribuir com uma análise crítica à viabilidade da aplicação do modelo em estudo, destacando-se no final algumas vantagens identificadas, bem como algumas dificuldades encontradas, que poderão ser superadas a partir de um conjunto de medidas aqui sugeridas.